148k views
2 votes
Evaluate f(x) = 4x + 3x^2 − 5 when x = -2.

23


-1


-25


-49

User Sbeliakov
by
4.7k points

1 Answer

1 vote

Answer:

f(-2) = -1

Explanation:

One way of doing this is to substitute -2 for x in every place where x shows up:

f(x) = 4x + 3x^2 − 5 → f(-2) = 4(-2) + 3(-2)^2 − 5

→ f(-2) = -8 + 3(4) - 5, or f(-2) = 4 - 5, or f(-2) = -1

User Jonathan Park
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.